2012
DOI: 10.1038/gt.2012.63
|View full text |Cite
|
Sign up to set email alerts
|

RPE65 gene therapy slows cone loss in Rpe65-deficient dogs

Abstract: Recent clinical trials of retinal pigment epithelium gene (RPE65) supplementation therapy in Leber congenital amaurosis type 2 patients have demonstrated improvements in rod and cone function, but it may be some years before the effects of therapy on photoreceptor survival become apparent. The Rpe65-deficient dog is a very useful pre-clinical model in which to test efficacy of therapies, because the dog has a retina with a high degree of similarity to that of humans. In this study, we evaluated the effect of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 69 publications
1
42
0
2
Order By: Relevance
“…Noninvasive OCT studies localized the region of preservation, and histological studies showed intact ONL and preservation of inner retinal layers. Our studies confirm and extend previous studies (14,17,35), and they support the hypothesis that, in RPE65-mutant dogs, early treatment of the primary RPE defect prevents the later onset of photoreceptor degeneration. Similar experiments in mutant mice treated early with gene therapy have shown survival of cone (12,13,15,16) and rod photoreceptors (49).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Noninvasive OCT studies localized the region of preservation, and histological studies showed intact ONL and preservation of inner retinal layers. Our studies confirm and extend previous studies (14,17,35), and they support the hypothesis that, in RPE65-mutant dogs, early treatment of the primary RPE defect prevents the later onset of photoreceptor degeneration. Similar experiments in mutant mice treated early with gene therapy have shown survival of cone (12,13,15,16) and rod photoreceptors (49).…”
Section: Discussionsupporting
confidence: 91%
“…To explain both findings, we postulate that there exists a critical limit in terms of accumulating molecular changes that are detrimental to photoreceptor survival under this condition of severe RPE65 dysfunction. There is evidence for molecular changes occurring in rod and cone photoreceptors in the predegenerative phase of RPE65 disease (17,18,32,54,58), and a specific translocation of one of the proapoptotic Bax isoforms from the cytosol to mitochondria has been observed to correlate with the initiation of photoreceptor cell loss (54,55). To date, there has been a paucity of murine studies of gene therapy in older animals after the onset of retina-wide rod degeneration (6,59).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This same logic could be used to explain the failure to halt degeneration in some previous animal studies (13,35). In support of this idea are gene therapy studies demonstrating a delay in photoreceptor degeneration that was limited to the transduced area (36)(37)(38).…”
Section: Creert2mentioning
confidence: 81%